Impact of pollution in Budha Nallah brook on the occurrence of fishes in river Satluj - Kaur, Tejinder (Indian Journal of Fisheries, 2011)
A study of Budha Nallah (BN) brook, a heavily polluted tributary of river Sutluj showed, the occurrence of 42 fish species in the upstream (US) region (8-10 km before the confluence of BN with the river) and 35 fish species in the downstream (DS) region (40-42 km following confluence of BN with the river). The confluence of BN with the river led to the disappearance of 7 fish species like Ambassis ranga, Amblypharyngodon mola, Catla catla, Ompok bimaculatus O. pabda, Punitus ticto and Xenentodon cancila whereas 8 fish species namely Aspidoparia morar, Chela bacaila, C. laubuca, Cirrhina reba, Crossocheilus latius, Osteobrama cotio, Puntius stigma and Trichogaster fasciatus are under the process of elimination as revealed by their low abundance in the DS region. The stretch between the point of confluence and area of collection in downstream region did not show occurrence of fishes indicating their absence in the region